2019
DOI: 10.20964/2019.06.05
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Polypyrrole/Reduced Graphene-Oxide Films for Electrochemical Capacitors

Abstract: The co-electrodeposition and characterization of Polypyrrole (PPy)/Reduced Graphene Oxide (RGO) films (1:5, 1:10 and 1:15 mass ratio) for electrochemical capacitors are presented in this work. Polypyrrole polymerization and incorporation of RGO were conducted simultaneously in order to attain the best possible dispersion of the latter within the polypyrrole matrix. The materials were characterized by scanning electron microscopy, Fourier-transform infrared spectroscopy, X-ray diffraction and electrochemical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The lower current obtained in the presence of GO was due to its low conductivity [24]. As the area of the cyclo voltammogram indicates the loading with active material [11], it was observed that the coatings contained less active material upon the addition of GO by CV deposition. The galvanostatic co-electrodeposition results confirmed the increased voltage necessary for deposition when GO is added.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The lower current obtained in the presence of GO was due to its low conductivity [24]. As the area of the cyclo voltammogram indicates the loading with active material [11], it was observed that the coatings contained less active material upon the addition of GO by CV deposition. The galvanostatic co-electrodeposition results confirmed the increased voltage necessary for deposition when GO is added.…”
Section: Discussionmentioning
confidence: 97%
“…The combination of materials such as conducting polymers with carbon nanomaterials has attracted increased interest in the last years in order to overcome the drawbacks these materials have as a singular component and improve their properties by synthesizing a hybrid material with a synergetic effect on properties including high energy and power density, cyclability [5], and stability [11]. For example, polypyrrole (PPy) is one of the most used conjugated polymers [10] in energy storage application [4], of an anionic surfactant could be employed to interact with the carboxyl groups of GO and separate layers of GO to exhibit improved performance [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation